Multifaceted investigation of Sulfamerazine: Insights from computational methods, experimental techniques, and molecular simulations - Ahmad, Seraj; Reeda, V.S. Jeba; Aziz, Kashif; Arora, Himanshu; Kumar, Manoj; Garima, Km; Ali, Akram; Shahid, Mudassar; Muthu, S.; Siddiqui, Nazia; Javed, Saleem (Journal of molecular structure, 2024)
•DFT and spectroscopic analysis of sulfamerazine Hirshfeld Surface, PED and MEP surface analysis.•FMO, UV-Vis analysis and NBO analysis for charge transfer studies.•Molecular docking and Molecular dynamic simulation of sulfamerazine with different Protein Receptors. The powerful sulfonamide antibiotic Sulfamerazine has been the subject of in-depth study to clarify its complex molecular interactions. In order to understand Sulfamerazine's pharmacological behaviour and interactions with biological components, this comprehensive study uses computational tools such as Density Functional Theory (DFT) calculations, spectroscopic analyses, and molecular docking simulations. Exploitation B3LYP/6-311++G(d,p) basis set, DFT simulations have provided important new understandings of the structure, vibrational properties, and binding mechanisms of this system. Vibrational assignments have been conducted by analyzing individual vibrational modes and comparing them to experimental data. The molecule's weak interactions have been identified grounded on electron density using Reduced Density Gradient Analysis. Fukui and MEP plot analyses have been employed to pinpoint the molecule's electrophilic and nucleophilic sites. Frontier molecular orbital analysis supported the observation of charge transfer within the molecule. Sulfamerazine is a viable option for further pharmaceutical development, as shown by drug-likeness and ADME (absorption, distribution, metabolism, and excretion) studies. In docking analysis, the inhibitor 6qzh stood out as particularly potent, capable of forming up to three hydrogen bonds, resulting in a binding energy of -8.2 kcal/mol. Molecular dynamics simulations have also shed light on the stability, solubility, and possible interactions of Sulfamerazine in diverse settings. This all-encompassing strategy promises to increase our understanding of the mechanism of action of Sulfamerazine, creating new opportunities for the logical development of more potent pharmaceuticals. [Display omitted]